2013
DOI: 10.1371/journal.pone.0077432
|View full text |Cite
|
Sign up to set email alerts
|

ω3-PUFAs Exert Anti-Inflammatory Activity in Visceral Adipocytes from Colorectal Cancer Patients

Abstract: ObjectiveThe aim of this study was to correlate specific fatty acid profiles of visceral white adipose tissue (WAT) with inflammatory signatures potentially associated with colorectal cancer (CRC).MethodsHuman adipocytes were isolated from biopsies of visceral WAT from 24 subjects subdivided in four groups: normal-weight (BMI 22.0-24.9 Kg/m2) and over-weight/obese (BMI 26.0-40.0 Kg/m2), affected or not by CRC. To define whether obesity and/or CRC affect the inflammatory status of WAT, the activation of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…For practical reasons we did not measure inflammatory responses in visceral fat, a depot known to be inherently more immune-cell infiltrated than subcutaneous fat. Some investigators have reported positive effects of v-3 fatty acid supplements on visceral fat (46,47), and others have noted that greater self-reported v-3 fatty acid intakes are negatively associated with visceral fat and percentage of body fat in healthy children (48). We cannot know whether there might have been a beneficial effect of v-3 fatty acids on visceral fat inflammation in our participants, but if there was it did not improve inflammatory markers (26) or insulin sensitivity.…”
Section: Discussionmentioning
confidence: 76%
“…For practical reasons we did not measure inflammatory responses in visceral fat, a depot known to be inherently more immune-cell infiltrated than subcutaneous fat. Some investigators have reported positive effects of v-3 fatty acid supplements on visceral fat (46,47), and others have noted that greater self-reported v-3 fatty acid intakes are negatively associated with visceral fat and percentage of body fat in healthy children (48). We cannot know whether there might have been a beneficial effect of v-3 fatty acids on visceral fat inflammation in our participants, but if there was it did not improve inflammatory markers (26) or insulin sensitivity.…”
Section: Discussionmentioning
confidence: 76%
“…However, DHA does not directly bind to this class of transcription factor. With respect to colon cancer, DHA exhibits a protective suppressive effect against hyperactivated STAT3 and may reestablish the equilibrium between STAT3 and PPARγ (42). The decrease in STAT3 activity may be associated with the ability of n-3 PUFA to trigger PPARγ-RXR heterodimers to localize at their cognate PPAR response elements and exchange corepressors for coactivators such as CREB binding protein and p300 (52).…”
Section: N-3 Pufa and Transcriptional Machinerymentioning
confidence: 99%
“…In this regard, it is of relevance that ω3/ω6 PUFA ratio of the industrialized diets is imbalanced, and this condition results in a well-known pro-inflammatory effect (22). Noteworthy, a decreased ω3/ω6 PUFA ratio of visceral AT correlates with AT inflammatory status in CRC patients suggesting that qualitative, more than quantitative, PUFA changes in AT may influence tissue dysfunctions potentially linked to inflammatory conditions (23). Likewise, the sum of some PUFA [i.e., gamma linolenic acid (GLA), Di-homo-gamma linolenic acid (DGLA), and arachidonic acid (AA)] in both visceral and subcutaneous AT was found statistically higher in cancer patients with respect to healthy controls (24).…”
Section: Dietary Polyunsaturated Fatty Acidsmentioning
confidence: 99%